Optimization of fermentation process for the production of intracellular polysaccharide from Paecilomyces cicadae and the immuno-stimulating activity of intracellular polysaccharide - Jun-Wen Cheng; Yan-Bin Wang; Liang He; Hua Qian; Li-Zhong Fu; Hai-Bo Li (World Journal of Microbiology and Biotechnology, 2012)

Coping with climate-induced water stresses through time and space in the mountains of Southwest China - Yufang Su; Jianchu Xu; Andy Wilkes; Juliet Lu; Qiaohong Li; Yao Fu; Xing Ma; R. Edward Grumbine (Regional Environmental Change, 2012)

Molecular Cloning and Characterization of Two 9-Lipoxygenase Genes from Taxus chinensis - Shu-tao Li; Meng Zhang; Chun-hua Fu; Sha Xie; Yu Zhang; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

A meta-analysis of the relationship between glutathione S-transferases gene polymorphism and hepatocellular carcinoma in Asian population - Jie Chen; Liang Ma; Ning-Fu Peng; Shi-Jun Wang; Le-Qun Li (Molecular Biology Reports, 2012)

Tetrodotoxin attenuates isoproterenol-induced hypertrophy in H9c2 rat cardiac myocytes - Ming-Zi Chen; Qing-Ting Bu; Shu-Chao Pang; Feng-Lan Li; Mei-Na Sun; Er-Fu Chu; Hui Li (Molecular and Cellular Biochemistry, 2012)

High density lipoprotein cholesterol promotes the proliferation of bone-derived mesenchymal stem cells via binding scavenger receptor-B type I and activation of PI3K/Akt, MAPK/ERK1/2 pathways - Jianfeng Xu; Juying Qian; Xinxing Xie; Li Lin; Jianying Ma; Zheyong Huang; Mingqiang Fu; Yunzeng Zou; Junbo Ge (Molecular and Cellular Biochemistry, 2012)

Molecular dynamic and quantum mechanics study of drug recognition for the extremity of DNA G-quadruplex groove - Jinlian Li; Jia Fu; Jianping Wang; Donghua Hu; Zhongmin Su; Xiaoqiang Jin (Medicinal Chemistry Research, 2012)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

Efficacy of endosulfan and fipronil and joint toxic action of endosulfan mixtures against Leptinotarsa decemlineata (Say) - Xiao-qin Shi; Man-Hui Xiong; Wei-Hua Jiang; Zhi-Tian Wang; Wen-Chao Guo; Zhen-Han Xia; Wen-Jun Fu; Guo-Qing Li (Journal of Pest Science, 2012)

Arsenic accumulation and distribution in the tissues of inbred lines in maize (Zea mays L.) - Z. H. Liu; W. H. Li; H. Y. Qi; G. L. Song; D. Ding; Z. Y. Fu; J. B. Liu; J. H. Tang (Genetic Resources and Crop Evolution, 2012)

Effects of Bacillus preparations on immunity and antioxidant activities in grass carp (Ctenopharyngodon idellus) - Li Weifen; Zhang Xiaoping; Song Wenhui; Deng Bin; Liang Quan; Fu Luoqin; Zheng Jiajia; Wang yue; Yu Dongyou (Fish Physiology and Biochemistry, 2012)

Effect of immunization with a recombinant cholera toxin B subunit/somatostatin fusion protein on immune response and growth hormone levels in mice - Bingbing Wu; Taoyan Yuan; Ruili Qi; Jun He; Yan Fu; Dong Niu; Weifen Li (Biotechnology Letters, 2012)

T-2 Toxin Contamination in Grains and Selenium Concentration in Drinking Water and Grains in Kaschin–Beck Disease Endemic Areas of Qinghai Province - Li-Yan Sun; Qiang Li; Fan-Gang Meng; Ying Fu; Zhi-Jun Zhao; Li-Hua Wang (Biological Trace Element Research, 2012)

Comparison of Effects of Vanadium Absorbed by Coprinus comatus with Those of Inorganic Vanadium on Bone in Streptozotocin-Diabetic Rats - Guangbin Wang; Ming He; Pei Yi; Jiashi Wang; Bin Li; Jianjun Li; Yonghui Fu; Lunhao Bai; Qin Fu (Biological Trace Element Research, 2012)

Development of RT-LAMP and real-time RT-PCR assays for the rapid detection of the new duck Tembusu-like BYD virus - Tao Jiang; Juan Liu; Yong-Qiang Deng; Jing-Liang Su; Li-Juan Xu; Zhi-Hui Liu; Xiao-Feng Li; Xue-Dong Yu; Shun-Ya Zhu; George Fu Gao; E-De Qin; Cheng-Feng Qin (Archives of Virology, 2012)

Simple and rapid detection of swine hepatitis E virus by reverse transcription loop-mediated isothermal amplification - Liang-Quan Zhang; Fu-Rong Zhao; Zhi-Gang Liu; Wei-Li Kong; Heng Wang; Yun Ouyang; Huan-Bin Liang; Chao-Yi Zhang; Hai-Tao Qi; Chang-Li Huang; Si-Hu Guo; Gui-Hong Zhang (Archives of Virology, 2012)

The variation of tree beta diversity across a global network of forest plots - Miquel De Cáceres; Pierre Legendre; Renato Valencia; Min Cao; Li‐Wan Chang; George Chuyong; Richard Condit; Zhanqing Hao; Chang‐Fu Hsieh; Stephen Hubbell; David Kenfack; Keping Ma; et al. (Global Ecology and Biogeography, 2012)
Aims With the aim of understanding why some of the world's forests exhibit higher tree beta diversity values than others, we asked: (1) what is the contribution of environmentally related variation versus pure spatial and local stochastic variation to tree beta diversity assessed at the forest plot scale; (2) at what resolution are these beta‐diversity components more apparent; and (3) what determines the variation in tree beta diversity observed across regions/continents? Location World‐wide. Methods We compiled an unprecedented data set of 10 large‐scale stem‐mapping forest plots differing in latitude, tree species richness and topographic variability. We assessed the tree beta diversity found within each forest plot separately. The non‐directional variation in tree species composition among cells of the plot was our measure of beta diversity. We compared the beta diversity of each plot with the value expected under a null model. We also apportioned the beta diversity into four components: pure topographic, spatially structured topographic, pure spatial and unexplained. We used linear mixed models to interpret the variation of beta diversity values across the plots. Results Total tree beta diversity within a forest plot decreased with increasing cell size, and increased with tree species richness and the amount of topographic variability of the plot. The topography‐related component of beta diversity was correlated with the amount of topographic variability but was unrelated to its species richness. The unexplained variation was correlated with the beta diversity expected under the null model and with species richness. Main conclusions Because different components of beta diversity have different determinants, comparisons of tree beta diversity across regions should quantify not only overall variation in species composition but also its components. Global‐scale patterns in tree beta diversity are largely coupled with changes in gamma richness due to the relationship between the latter and the variation generated by local stochastic assembly processes.

An Effective Approach to Long-Term Optimal Operation of Large-Scale Reservoir Systems: Case Study of the Three Gorges System - Fang-Fang Li; Jia-Hua Wei; Xu-Dong Fu; Xin-Yu Wan (Water Resources Management, 2012)

Identification and characterization of the soybean IPK1 ortholog of a low phytic acid mutant reveals an exon-excluding splice-site mutation - Feng-Jie Yuan; Dan-Hua Zhu; Yuan-Yuan Tan; De-Kun Dong; Xu-Jun Fu; Shen-Long Zhu; Bai-Quan Li; Qing-Yao Shu (Theoretical and Applied Genetics, 2012)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

Characteristic, composition, and sources of TSP investigated by HRTEM/EDS and ESEM/EDS - Yunbo Zhai; Zongmin Fu; Lafang Wang; Guangming Zeng; Caiting Li; Hongmei Chen; Yuanming Lan; Pei Lu (Environmental Monitoring and Assessment, 2012)

Characterization of carbonic anhydrase II from Chlorella vulgaris in bio-CO2 capture - Li Li; Ming-lai Fu; Yong-hao Zhao; Yun-tian Zhu (Environmental Science and Pollution Research, 2012)

Speciation distribution and mass balance of copper and zinc in urban rain, sediments, and road runoff - XiaoJun Zuo; DaFang Fu; He Li (Environmental Science and Pollution Research, 2012)

Roseibacterium beibuensis sp. nov., a Novel Member of Roseobacter Clade Isolated from Beibu Gulf in the South China Sea - Yujiao Mao; Jingjing Wei; Qiang Zheng; Na Xiao; Qipei Li; Yingnan Fu; Yanan Wang; Nianzhi Jiao (Current Microbiology, 2012)

Constraints on timing and origin of the Dayinjian intrusion and associated molybdenum mineralization, western Dabie orogen, central China - Hongchao Li; Zhaowen Xu; Xiancai Lu; Wei Chen; Wenjun Qu; Bin Fu; Xiaonan Yang; Jie Yang; Jinquan Chen (International Geology Review, 2012)

RETRACTED ARTICLE: A 2-D DIGE analysis of simulated acid rain-responsive proteins in Pinus massoniana needles - Ting-Wu Liu; Wen-Jun Hu; Xiao-Qin Wang; Li Niu; Bin Fu; Fei-Hua Wu; Zhen-Ming Pei; Hai-Lei Zheng (Trees, 2012)

Enhancing Taxol Biosynthesis by Overexpressing a 9-Cis-Epoxycarotenoid Dioxygenase Gene in Transgenic Cell Lines of Taxus chinensis - Shu-tao Li; Chun-hua Fu; Meng Zhang; Yu Zhang; Sha Xie; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

Erratum to: Validation of reference genes for real-time quantitative PCR normalization in soybean developmental and germinating seeds - Qing Li; Cheng-Ming Fan; Xiao-Mei Zhang; Yong-Fu Fu (Plant Cell Reports, 2012)

A novel dirigent protein gene with highly stem-specific expression from sugarcane, response to drought, salt and oxidative stresses - Guo Jin-long; Xu Li-ping; Fang Jing-ping; Su Ya-chun; Fu Hua-ying; Que You-xiong; Xu Jing-sheng (Plant Cell Reports, 2012)

Validation of reference genes for real-time quantitative PCR normalization in soybean developmental and germinating seeds - Qing Li; Cheng-Ming Fan; Xiao-Mei Zhang; Yong-Fu Fu (Plant Cell Reports, 2012)

Novel glycine-dependent inactivation of NMDA receptors in cultured hippocampal neurons - Yun-Feng Zhang; Xia Li; Liang-Liang Peng; Guo-Hua Wang; Kai-Fu Ke; Zheng-Lin Jiang (Neuroscience Bulletin, 2012)

Clinical significance of detection of antibodies to fetal and adult acetylcholine receptors in myasthenia gravis - Qi-Guang Shi; Zhi-Hong Wang; Xiao-Wei Ma; Da-Qi Zhang; Chun-Sheng Yang; Fu-Dong Shi; Li Yang (Neuroscience Bulletin, 2012)

Origin of the Maoduan Pb–Zn–Mo deposit, eastern Cathaysia Block, China: geological, geochronological, geochemical, and Sr–Nd–Pb–S isotopic constraints - Yan-Jun Li; Jun-Hao Wei; Hua-Yong Chen; Jun Tan; Le-Bing Fu; Gang Wu (Mineralium Deposita, 2012)

Abundance and composition of ammonia-oxidizing bacteria and archaea in different types of soil in the Yangtze River estuary - Xiao-ran Li; Yi-ping Xiao; Wen-wei Ren; Zeng-fu Liu; Jin-huan Shi; Zhe-xue Quan (Journal of Zhejiang University-SCIENCE B, 2012)

Effect of feeding on the function and structure of the digestive system in juvenile southern catfish (Silurus meridionalis Chen) - Ling-Qing Zeng; Feng-Jie Li; Shi-Jian Fu; Zhen-Dong Cao; Yao-Guang Zhang (Fish Physiology and Biochemistry, 2012)

Genetic analysis of early growth traits of the triangle shell mussel, Hyriopsis Cumingii, as an insight for potential genetic improvement to pearl quality and yield - Wu Jin; Zhiyi Bai; Longlong Fu; Genfang Zhang; Jiale Li (Aquaculture International, 2012)

An in vivo study with an MRI tracer method reveals the biophysical properties of interstitial fluid in the rat brain - HongBin Han; Kai Li; JunHao Yan; Kai Zhu; Yu Fu (Science China Life Sciences, 2012)

Molecular biomarkers of colorectal cancer: prognostic and predictive tools for clinical practice - Wei-qin Jiang; Fang-fang Fu; Yang-xia Li; Wei-bin Wang; Hao-hao Wang; Hai-ping Jiang; Li-song Teng (Journal of Zhejiang University-SCIENCE B, 2012)

Neuroprotection by Silencing iNOS Expression in a 6-OHDA Model of Parkinson’s Disease - Min Li; Fu-rong Dai; Xiao-ping Du; Qi-dong Yang; Yuxiang Chen (Journal of Molecular Neuroscience, 2012)

Analysis of QTL for yield-related traits in cassava using an F1 population from non-inbred parents - Xin Chen; Yuhua Fu; Zhiqiang Xia; Li Jie; Haiyan Wang; Cheng Lu; Wenquan Wang (Euphytica, 2012)

Comparison study between observation and simulation for sea fog over the Yellow Sea in May 2009 - Dan Fu; Shuai Wang; Delin Chen; Huaji Pang; Pengyuan Li (Journal of Ocean University of China, 2012)

Signal-purity-spectrum-based colored deconvolution - Guo-Fa Li; Geng-Xin Peng; Ying Yue; Wan-Li Wang; Yong-Fu Cui (Applied Geophysics, 2012)

A Novel Method for Automatic Identification of Motion Artifact Beats in ECG Recordings - Yuewen Tu; Xiuquan Fu; Dingli Li; Chao Huang; Yawei Tang; Shuming Ye; Hang Chen (Annals of Biomedical Engineering, 2012)

Effects of fertilization and drought stress on tannin biosynthesis of Casuarina equisetifolia seedlings branchlets - Li Hua Zhang; Hong Bo Shao; Gong Fu Ye; Yi Ming Lin (Acta Physiologiae Plantarum, 2012)

New perspective of Miocene marine hydrocarbon source rocks in deep-water area in Qiongdongnan Basin of northern South China Sea - Wenhao Li; Zhihuan Zhang; Youchuan Li; Ning Fu (Acta Oceanologica Sinica, 2012)

Anomalous temperature–growth response of Abies faxoniana to sustained freezing stress along elevational gradients in China’s Western Sichuan Province - Zong Shan Li; Guo Hua Liu; Bo Jie Fu; Chan Juan Hu; Shu Zheng Luo; Xing Liang Liu; Fei He (Trees, 2012)

Molecular characterization of the PpMADS1 gene from peach - Cui Li; Hua Xie; Lin Zhang; Yong Xu; Yun-Fu Li; Rong-Cai Ma (Tree Genetics & Genomes, 2012)

Identification of FAD2 and FAD3 genes in Brassica napus genome and development of allele-specific markers for high oleic and low linolenic acid contents - Qingyong Yang; Chuchuan Fan; Zhenhua Guo; Jie Qin; Jianzhong Wu; Qingyuan Li; Tingdong Fu; Yongming Zhou (Theoretical and Applied Genetics, 2012)

Developmental, cytological and transcriptional analysis of autotetraploid Arabidopsis - Xiaodong Li; Erru Yu; Chuchuan Fan; Chunyu Zhang; Tingdong Fu; Yongming Zhou (Planta, 2012)

Partial antiviral activities of the Asn631 chicken Mx against newcastle disease virus and vesicular stomatitis virus - Bichun Li; Dezhi Fu; Yani Zhang; Qi Xu; Ligang Ni; Guobin Chang; Mengmeng Zheng; Bo Gao; Huaichang Sun; Guohong Chen (Molecular Biology Reports, 2012)

Hydrocarbon- and ore-bearing basinal fluids: a possible link between gold mineralization and hydrocarbon accumulation in the Youjiang basin, South China - X. X. Gu; Y. M. Zhang; B. H. Li; S. Y. Dong; C. J. Xue; S. H. Fu (Mineralium Deposita, 2012)

Correlation between plasma amino acid profiles and the various stages of hepatitis B infection - J. Yang; J. He; H. Cao; X. Zhao; S. Fu; H. Lu; Y. Chen; X. Pan; L. Li (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Biosorption of zinc and copper from aqueous solutions by two freshwater green microalgae Chlorella pyrenoidosa and Scenedesmus obliquus - Guang-Jie Zhou; Fu-Qiang Peng; Li-Juan Zhang; Guang-Guo Ying (Environmental Science and Pollution Research, 2012)

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

Construction of Escherichia coli strains producing l-serine from glucose - Yu Li; Gu-Kui Chen; Xin-Wei Tong; Hui-Tu Zhang; Xiao-Guang Liu; Yi-Han Liu; Fu-Ping Lu (Biotechnology Letters, 2012)

Comparative mapping reveals similar linkage of functional genes to QTL of yield-related traits between Brassica napus and Oryza sativa - FUPENG LI; CHAOZHI MA; QINGFANG CHEN; TOUMING LIU; JINXIONG SHEN; JINXING TU; YONGZHONG XING; TINGDONG FU (Journal of Genetics, 2012)

Detrital zircon U-Pb geochronology and its provenance implications on Silurian Tarim basin - Jingyan Liu; Changsong Lin; Sitian Li; Zhenzhong Cai; Shiqiang Xia; Chao Fu; Yongquan Liu (Journal of Earth Science, 2012)

Estimation of regional evapotranspiration in alpine area and its response to land use change: A case study in Three-River Headwaters region of Qinghai-Tibet Plateau, China - Huixia Li; Guohua Liu; Bojie Fu (Chinese Geographical Science, 2012)

Effect of extreme value loss on long-term correlated time series - Naiming Yuan; Zuntao Fu; Huiqun Li; Jiangyu Mao (Theoretical and Applied Climatology, 2012)

Assessment of genetic and epigenetic variation during long-term Taxus cell culture - Chunhua Fu; Liqin Li; Wenjuan Wu; Maoteng Li; Xiaoqing Yu; Longjiang Yu (Plant Cell Reports, 2012)

Celecoxib inhibits growth of human autosomal dominant polycystic kidney cyst-lining epithelial cells through the VEGF/Raf/MAPK/ERK signaling pathway - Tao Xu; Nian-Song Wang; Li-Li Fu; Chao-Yang Ye; Sheng-Qiang Yu; Chang-Lin Mei (Molecular Biology Reports, 2012)

Characterization of transcriptional activation and inserted-into-gene preference of various transposable elements in the Brassica species - Caihua Gao; Meili Xiao; Lingyan Jiang; Jiana Li; Jiaming Yin; Xiaodong Ren; Wei Qian; Ortegón Oscar; Donghui Fu; Zhanglin Tang (Molecular Biology Reports, 2012)

Sphingosine 1-phosphate acts as an activator for the porcine Gpr3 of constitutively active G protein-coupled receptors - Bao-le Zhang; Ye Li; Jian-hua Ding; Fu-lu Dong; Yan-jun Hou; Bao-chun Jiang; Fang-xiong Shi; Yin-xue Xu (Journal of Zhejiang University-SCIENCE B, 2012)

Structural insights into a human anti-IFN antibody exerting therapeutic potential for systemic lupus erythematosus - Songying Ouyang; Bin Gong; Jin-Zhi Li; Li-Xia Zhao; Wei Wu; Fu-Shun Zhang; Lina Sun; Shu-Jun Wang; Meng Pan; Chuan Li; Wenguang Liang; Neil Shaw; et al. (Journal of Molecular Medicine, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Pyrosequencing of a short fragment of the amelogenin gene for gender identification - Shujin Li; Ting Feng; Lihong Fu; Zhenhua Li; Chunguang Lou; Xiaojing Zhang; Chunling Ma; Bin Cong (Molecular Biology Reports, 2012)

Effect of active immunization against a recombinant mouse granulocyte-macrophage colony-stimulating factor/somatostatin fusion protein on the growth of mice - Bingbing Wu; Ruili Qi; Bin Li; Taoyan Yuan; Heshan Liu; Jun He; Zhiwei Lin; Weifen Li; Yan Fu; Dong Niu (Molecular Biology Reports, 2012)

A role for anti-CD45RB monoclonal antibody treatment upon dendritic cells - Hui Qi; Jin-Peng Liu; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2012)

Computational prediction and experimental assessment of an HLA-A*0201-restricted cytotoxic T lymphocyte epitope from neutral endopeptidase - Jingbo Zhang; Zhengcai Jia; Zhihua Lin; Jingyi Li; Xiaolan Fu; Yunjian Huang; Jinghong Zhao; Ling Nie; Weiping Hou; Fahuan Yuan; Yuzhang Wu (Immunologic Research, 2012)

Human influence on the population decline and loss of genetic diversity in a small and isolated population of Sichuan snub-nosed monkeys (Rhinopithecus roxellana) - Zong Fei Chang; Mao Fang Luo; Zhi Jin Liu; Jing Yuan Yang; Zuo Fu Xiang; Ming Li; Linda Vigilant (Genetica, 2012)

Effects of alfalfa and organic fertilizer on benzo[a]pyrene dissipation in an aged contaminated soil - Dengqiang Fu; Ying Teng; Yongming Luo; Chen Tu; Shixing Li; Zhengao Li; Peter Christie (Environmental Science and Pollution Research, 2012)

Mechanisms of action of mesenchymal stem cells in cutaneous wound repair and regeneration - HaiHong Li; Xiaobing Fu (Cell and Tissue Research, 2012)

Evaluation of laser labeling on growth and survival of the freshwater pearl mussel, Hyriopsis cumingii - Longlong Fu; Zhiyi Bai; Wu Jin; Genfang Zhang; Jiale Li (Aquaculture International, 2012)

Edge enhancement of gravity anomalies and gravity gradient tensors using an improved small sub-domain filtering method - Fu-Yu Jiang; Li-Kun Gao (Applied Geophysics, 2012)

Improved LASSO priors for shrinkage quantitative trait loci mapping - Ming Fang; Dan Jiang; Dandan Li; Runqing Yang; Weixuan Fu; Lijun Pu; Huijiang Gao; Guihua Wang; Liyun Yu (Theoretical and Applied Genetics, 2012)

A Comparison Study Between Spring and Summer Fogs in the Yellow Sea-Observations and Mechanisms - Suping Zhang; Man Li; Xiangui Meng; Gang Fu; Zhaopeng Ren; Shanhong Gao (Pure and Applied Geophysics, 2012)

Large-Scale Environmental Influences on the Onset, Maintenance, and Dissipation of Six Sea Fog Cases over the Yellow Sea - Pengyuan Li; Gang Fu; Chungu Lu (Pure and Applied Geophysics, 2012)

The chloroplast ribosomal protein L21 gene is essential for plastid development and embryogenesis in Arabidopsis - Tuanzhang Yin; Gang Pan; Han Liu; Jian Wu; Yongpeng Li; Zhenxing Zhao; Tingdong Fu; Yongming Zhou (Planta, 2012)

Risk evaluation of China’s natural disaster systems: an approach based on triangular fuzzy numbers and stochastic simulation - Ju-Liang Jin; Yi-Ming Wei; Le-Le Zou; Li Liu; Juan Fu (Natural Hazards, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Association of CTLA-4 gene polymorphisms with sporadic breast cancer risk and clinical features in Han women of Northeast China - Dalin Li; Qiujin Zhang; Fengyan Xu; Zhenkun Fu; Weiguang Yuan; Dianjun Li; Da Pang (Molecular and Cellular Biochemistry, 2012)

Fluorescence microscopic analysis of bone osseointegration of strontium-substituted hydroxyapatite implants - Dan-li Fu; Qiao-hong Jiang; Fu-ming He; Guo-li Yang; Li Liu (Journal of Zhejiang University-SCIENCE B, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

Ischemia hypothermia improved contractility under normothermia reperfusion in the model of cultured cardiomyocyte - Heng Li; Xiangshao Fang; Zhengfei Yang; Yue Fu; Yu Wang; Jinlang Wu; Tao Yu; Zitong Huang (In Vitro Cellular & Developmental Biology - Animal, 2012)

Quantifying the Effects of Conservation Practices on Soil, Water, and Nutrients in the Loess Mesa Ravine Region of the Loess Plateau, China - Xiang-Zhou Xu; Mei-Juan Li; Bin Liu; Shang-Fu Kuang; Shi-Guo Xu (Environmental Management, 2012)

Phytotoxicity of Thiocyanate to Rice Seedlings - Xiao-Zhang Yu; Fu-Zhong Zhang; Fan Li (Bulletin of Environmental Contamination and Toxicology, 2012)

Identification of volatile components in yak butter using SAFE, SDE and HS-SPME-GC/MS - Ning Li; Bao-Guo Sun; Fu-Ping Zheng; Hai-Tao Chen; Si-Yuan Liu; Chen Gu; Zhen-Yang Song (Natural Product Research, 2012)

Simultaneous quantification of lopinavir and ritonavir in human plasma by high performance liquid chromatography coupled with UV detection - HuiJuan Kou; Min Ye; Qiang Fu; Yang Han; XiaoLi Du; Jing Xie; Zhu Zhu; TaiSheng Li (Science China Life Sciences, 2012)

A new analysis of testicular proteins through integrative bioinformatics - Liu Fu-Jun; Wang Hai-Yan; Li Jian-Yuan (Molecular Biology Reports, 2012)

Suppression of lung cancer metastasis-related protein 1 (LCMR1) inhibits the growth of colorectal cancer cells - E Ji-Fu; Jun-Jie Xing; Li-Qiang Hao; Chuan-Gang Fu (Molecular Biology Reports, 2012)

Identification of microRNA-like RNAs in a plant pathogenic fungus Sclerotinia sclerotiorum by high-throughput sequencing - Jiahong Zhou; Yanping Fu; Jiatao Xie; Bo Li; Daohong Jiang; Guoqing Li; Jiasen Cheng (Molecular Genetics and Genomics, 2012)

Protective effects of 7-difluoromethyl-5,4′-dimethoxygenistein against human aorta endothelial injury caused by lysophosphatidyl choline - Fei Liu; Jian-Guo Cao; Cheng Li; Jin-Seng Tan; Xiao-Hua Fu (Molecular and Cellular Biochemistry, 2012)

Natural populations of lactic acid bacteria in douchi from Yunnan Province, China - Chen-jian Liu; Fu-ming Gong; Xiao-ran Li; Hai-yan Li; Zhong-hua Zhang; Yue Feng; Hiroko Nagano (Journal of Zhejiang University-SCIENCE B, 2012)

Oceaniovalibus guishaninsula gen. nov., sp. nov., A Marine Bacterium of the Family Rhodobacteraceae - Keshao Liu; Rui Zong; Qipei Li; Yingnan Fu; Yongle Xu; Yanan Wang; Nianzhi Jiao (Current Microbiology, 2012)

Comparative Screening of K-ras Mutations in Colorectal Cancer and Lung Cancer Patients Using a Novel Real-Time PCR with ADx-K-ras Kit and Sanger DNA Sequencing - Haiping Zhang; Xiongwei Zheng; Tianhai Ji; Li Fu; Dongyu Bai; Yongqiang Liao; Haifang Zhang; Yi Ding; Limou Zheng (Cell Biochemistry and Biophysics, 2012)

A fuzzy-Markov-chain-based analysis method for reservoir operation - D. Z. Fu; Y. P. Li; G. H. Huang (Stochastic Environmental Research and Risk Assessment, 2012)

TH1, a DUF640 domain-like gene controls lemma and palea development in rice - Xiaojiao Li; Lianjun Sun; Lubin Tan; Fengxia Liu; Zuofeng Zhu; Yongcai Fu; Xianyou Sun; Xuewen Sun; Daoxin Xie; Chuanqing Sun (Plant Molecular Biology, 2012)

Molecular characterization and expression analysis of dihydroflavonol 4-reductase (DFR) gene in Saussurea medusa - Houhua Li; Jian Qiu; Fudong Chen; Xiaofen Lv; Chunxiang Fu; Dexiu Zhao; Xuejun Hua; Qiao Zhao (Molecular Biology Reports, 2012)

Polymorphisms of KiSS-1 and GPR54 genes and their relationships with litter size in sheep - Mingxing Chu; Chaoting Xiao; Tao Feng; Yan Fu; Guiling Cao; Li Fang; Ran Di; Qianqian Tang; Dongwei Huang; Yuehui Ma; Kui Li; Ning Li (Molecular Biology Reports, 2012)

DJ-1 may contribute to metastasis of non-small cell lung cancer - Jing Bai; Changlong Guo; Wenjing Sun; Ming Li; Xiangning Meng; Yang Yu; Yan Jin; Dandan Tong; Jingshu Geng; Qi Huang; Jiping Qi; Songbin Fu (Molecular Biology Reports, 2012)

Integrin-mediated signaling contributes to gadolinium-containing-particle-promoted cell survival and G1 to S phase cell cycle transition by enhancing focal adhesion formation - Jin-Xia Li; Li-Juan Fu; Xiao-Gai Yang; Kui Wang (JBIC Journal of Biological Inorganic Chemistry, 2012)

The monitoring results of electromagnetic radiation of 110-kV high-voltage lines in one urban location in Chongqing P.R. China - Qi-zhong Qin; Yu Chen; Ting-ting Fu; Li Ding; Ling-li Han; Jian-chao Li (Environmental Monitoring and Assessment, 2012)

Mutations in isocitrate dehydrogenase 2 accelerate glioma cell migration via matrix metalloproteinase-2 and 9 - Yuejun Fu; Yali Zheng; Ke Li; Rui Huang; Shuhua Zheng; Na An; Aihua Liang (Biotechnology Letters, 2012)

Transdifferentiation of human adipose-derived stem cells into urothelial cells: potential for urinary tract tissue engineering - Jian-Guo Shi; Wei-Jun Fu; Xiao-Xiong Wang; Yong-De Xu; Gang Li; Bao-Fa Hong; Kun Hu; Fu-Zhai Cui; Yan Wang; Xu Zhang (Cell and Tissue Research, 2012)

Variational retrieval of leaf area index from MODIS time series data: examples from the Heihe river basin, north-west China - Zhiqiang Xiao; Jindi Wang; Shunlin Liang; Hongmin Zhou; Xijia Li; Liqiang Zhang; Ziti Jiao; Yan Liu; Zhuo Fu (International Journal of Remote Sensing, 2012)

A modified visual loop-mediated isothermal amplification method for diagnosis and differentiation of main pathogens from Mycobacterium tuberculosis complex - Ming Hong; Lei Zha; Wenliang Fu; Minji Zou; Wuju Li; Donggang Xu (World Journal of Microbiology and Biotechnology, 2012)

Cloning and characterization of a maize bZIP transcription factor, ZmbZIP72, confers drought and salt tolerance in transgenic Arabidopsis - Sheng Ying; Deng-Feng Zhang; Jing Fu; Yun-Su Shi; Yan-Chun Song; Tian-Yu Wang; Yu Li (Planta, 2012)

The reduction of reactive oxygen species formation by mitochondrial alternative respiration in tomato basal defense against TMV infection - Yang-Wen-Ke Liao; Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; De-Kun Dong; Yu-Ping Jiang; Yan-Hong Zhou; Xiao-Jian Xia; Wu-Sheng Liang; Jing-Quan Yu (Planta, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

CDH1 promoter polymorphism and stomach cancer susceptibility - Yi-Ling Li; Zhong Tian; Jian-Bing Zhang; Bao-Yu Fu (Molecular Biology Reports, 2012)

Signal transduction during cold, salt, and drought stresses in plants - Guo-Tao Huang; Shi-Liang Ma; Li-Ping Bai; Li Zhang; Hui Ma; Ping Jia; Jun Liu; Ming Zhong; Zhi-Fu Guo (Molecular Biology Reports, 2012)

A novel SNP of liver-type fatty acid-binding protein gene in duck and its associations with the intramuscular fat - Jun He; Jiucheng Chen; Lizhi Lu; Yong Tian; Zhengrong Tao; Deqian Wang; Jinjun Li; Guoqin Li; Junda Shen; Yan Fu; Dong Niu (Molecular Biology Reports, 2012)

Orbilia blumenaviensis and its Arthrobotrys anamorph - Min Qiao; Ying Zhang; Shi-Fu Li; H.-O. Baral; E. Weber; Hong-Yan Su; Jian-Ping Xu; Ke-Qin Zhang; Ze-Fen Yu (Mycological Progress, 2012)

Norcantharidin, a protective therapeutic agent in renal tubulointerstitial fibrosis - Ying Li; Yan Ge; Fu You Liu; You Ming Peng; Lin Sun; Jun Li; Qiong Chen; Yan Sun; Kun Ye (Molecular and Cellular Biochemistry, 2012)

Systematic assessment and meta-analysis of the efficacy and safety of fasudil in the treatment of cerebral vasospasm in patients with subarachnoid hemorrhage - Guang Jian Liu; Zheng Jun Wang; Yun Fu Wang; Li Li Xu; Xiao Ling Wang; Yong Liu; Guo Jun Luo; Guo Hou He; Yan Jun Zeng (European Journal of Clinical Pharmacology, 2012)

Analysis of ESTs from a Normalized cDNA Library of the Rhizome Tip of Oryza longistaminata - Ting Zhang; Lijuan Li; Fengyi Hu; Xiuqin Zhao; Binying Fu; Daichang Yang (Journal of Plant Biology, 2012)

Speciation in the Rana chensinensis species complex and its relationship to the uplift of the Qinghai–Tibetan Plateau - WEI‐WEI ZHOU; YANG WEN; JINZHONG FU; YONG‐BIAO XU; JIE‐QIONG JIN; LI DING; MI‐SOOK MIN; JING CHE; YA‐PING ZHANG (Molecular Ecology, 2012)
Speciation remains a fundamental issue in biology. Herein, we report an investigation into speciation in the Rana chensinensis species complex using DNA sequence data from one mitochondrial and five nuclear genes. A phylogenetic analysis of the data revealed four major clades in the complex, and each of them was found to likely represent a species, including one cryptic species. Ecological niche models were generated from 19 climatic variables for three of the four major clades, which were represented by widespread sampling, including R. chensinensis , Rana kukunoris and the potential cryptic species. Each clade is associated with a unique ecological unit, and this indicates that ecological divergence probably drove speciation. Ecological divergence is likely related to the late Cenozoic orogenesis of the Qinghai–Tibetan Plateau. In addition, gene flow between species was detected but only in peripheral portions of the ranges of the four major clades, thus likely had little influence on the speciation processes. Discordances between mitochondrial and nuclear genes were also found; the nominal species, R. chensinensis , contains multiple maternal clades, suggesting potential mitochondrial introgression between R. chensinensis and R. kukunoris .

Synthesis of (–)-arctigenin derivatives and their anticancer activity - Chen Gui-Rong; Cai Li-Ping; Dou De-Qiang; Kang Ting-Guo; Li Hong-Fu; Li Fu-Rui; Jiang Ning (Natural Product Research, 2012)

Effect of dirhamnolipid on the removal of phenol catalyzed by laccase in aqueous solution - Zhi-Feng Liu; Guang-Ming Zeng; Hua Zhong; Xing-Zhong Yuan; Hai-Yan Fu; Mei-Fang Zhou; Xiao-Ling Ma; Hui Li; Jian-Bing Li (World Journal of Microbiology and Biotechnology, 2012)

The Kalatongke magmatic Ni–Cu deposits in the Central Asian Orogenic Belt, NW China: product of slab window magmatism? - Chusi Li; Mingjie Zhang; Piaoer Fu; Zhuangzhi Qian; Peiqing Hu; Edward M. Ripley (Mineralium Deposita, 2012)

Studies on chemical fingerprints of Siraitia grosvenorii fruits (Luo Han Guo) by HPLC - Fenglai Lu; Dianpeng Li; Chuanming Fu; Jinlei Liu; Yonglin Huang; Yueyuan Chen; Yongxin Wen; Toshihiro Nohara (Journal of Natural Medicines, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

Silicate-Mediated Alleviation of Pb Toxicity in Banana Grown in Pb-Contaminated Soil - Libin Li; Cheng Zheng; Youqiang Fu; Daoming Wu; Xujian Yang; Hong Shen (Biological Trace Element Research, 2012)

Origin of hydrogen peroxide during the cowpea- Xanthomonas interaction - Yan Zhu; Yanhong Li; Ronghui Hu; Yani Zheng; Na Feng; Fu Chen; Jing Wang; Hongyu Li (Australasian Plant Pathology, 2012)

Comparative full-length sequence analysis of Marek’s disease virus vaccine strain 814 - Feng Zhang; Chang-Jun Liu; Yan-Ping Zhang; Zhi-Jie Li; Ai-Ling Liu; Fu-Hai Yan; Feng Cong; Yun Cheng (Archives of Virology, 2012)